The Rights and Status of Widows in Islam: A Study from the Perspective of Multicultural Islamic Education in the Context of Bangladesh - Mahmudulhassan, M; Waston, W; Nirwana AN, Andri (Multicultural Islamic Education Review, 2023)
One of the most discussed topics in today’s society is the issue of widows’ proper rights and status. This research paper investigates the rights and status of widows within the framework of Islamic education in the context of Bangladesh using qualitative methods. It included the Qur’an, Hadith, and various forms of research.  Islam has given them a detailed discussion of their rights and dignity just like any other woman. Widows often face unique challenges and social stigmatization in various societies, and this study focuses on understanding their rights and status as prescribed by Islamic teachings and the extent to which these teachings are implemented within the realm of Islamic education. Bangladesh government has fixed some allowance for them which is very little. No steps have been taken to increase employment to make them economically prosperous. This paper contributes to the ongoing discourse on women’s rights within an Islamic context and highlights the significance of integrating such discussions within the education system for tangible societal transformation.